Achieving remarkable and reversible mechanochromism from a bright ionic AIEgen with high specificity for mitochondrial imaging and secondary aggregation emission enhancement for long-term tracking of tumors. (5th February 2020) - Yang, Xinzhe; Wang, Qian; Hu, Peiyu; Xu, Chao; Guo, Wenjing; Wang, Zhi; Mao, Zhu; Yang, Zhan; Liu, Cong; Shi, Guang; Chen, Ling; Xu, Bingjia; et al.
Abstract : An ionic AIEgen with high fluorescence quantum yield shows remarkable and reversible mechanochromism as well as excellent mitochondrial imaging of cancer cells and long-term tracking of tumors. Abstract : Strong intermolecular interactions that are in favour of elevating the luminescence efficiencies of aggregation-induced emission luminogens (AIEgens) are usually detrimental to the generation of obvious mechanochromism (MC). Therefore, it remains a challenge to develop MC-active AIE compounds that show high fluorescence quantum yield and a significant emission wavelength change simultaneously. Herein, a purely organic AIEgen and its ionic species, namely, TCPy and TCPyP, have been constructed by simultaneously employing tetraphenylethene (TPE) and phenylacrylonitrile as essential chromophores. It is found that both luminogens are highly emissive in the solid state and afford content Φ F, s values of 0.90 and 0.52, respectively. Concurrently, TCPy has been determined to possess mechanochromism (MC) properties, but only gives a small emission variation of 14 nm under mechanical stimuli. By contrast, TCPyP exhibits remarkable and reversible MC with a large Δ λ em, max value of up to 90 nm, representing the state-of-the-art MC performance for ionic AIEgens. Single crystal analysis reveals that the prominent MC of TCPyP mainly originates from the presence of bulky hexafluorophosphate anions in the crystal structure, which can enlarge the intermolecular distance to slightly weaken the intermolecular interactions and thereby result in the transformation of H-aggregates to J-aggregates upon grinding treatment. Besides, TCPyP shows much higher mitochondrial specificity in comparison with TCPy and enables mitochondrial staining with high brightness and good biocompatibility in living cells. Moreover, an abnormal phenomenon of secondary aggregation emission enhancement is observed by using this ionic AIEgen as a bioprobe for in vivo imaging, which allows long-term tracking of the tumor in nude mice. All these results suggest that the ionic AIEgen TCPyP has potential for various practical applications, including sensing, anti-counterfeiting, cell imaging and cancer diagnosis.